Relation Visualization of Environmental Quality Index with Environmental Resource Indicators Using Multiple Indicators Multiple Causes Model - Mardhotillah, Bunga; Zurweni, Zurweni; Elisa, Edi; Alim, Khairul (Universitas Jambi, 2023)
This research aims to visualize the model of environmental resource factors on the constituent factors of the environmental quality index using the multiple indicators multiple causes (MIMIC) method, using secondary data sourced from IKLH 2020. The predictor variables in this study include air quality, water quality, land cover quality, and environmental quality. Some of the indicators in this research are Conservation Forest Area, Limited Production Forest Area, Fixed Production Forest Area, Protection Forest Area, Coral Reefs, and Mangroves. Data Analysis using MIMIC Model generated by JASP Software, showing a very significant baseline and model factor. Some predictor coefficients have low standard error (close to zero), as well as significant indicators coefficients, except coral reefs, with a p-value of 0.736. The form model is worth using, since the RMSEA is worth 0.188. With a P-Value of 0.005. A high R-Squared is given by two indicators, namely Limited Production Forest Area, and Fixed Production Forest Area, respectively valued at 0.968 and 0.790